Inusitada descoberta : o valor probatório do encontro fortuito nas interceptações das comunicações telefônicas - Carvalho, Fernanda Moura de (2007)
Art. 5º of the Federal Constitution was regulated by the Law nº 9296/96. The Law, however, over all did not contemplate the hypothesis of the fortuitous meeting in telephonic interceptions that are sufficient ocorrente, in reason of the complexity of crime and the advance of the technology of the information. It moves in legislative process, first draft of reform of the Law above cited. In this, it has the forecast of unusual discoveries In this, it has the forecast of unusual discoveries, however only in the hypotheses that the doctrine stipulated to call inquiry knowledge. The Law that will be able to avenge silences, again, how much to the hypothesis of the fortuitous meeting properly said. From the analysis of the constitucional law to the secrecy, of the principle of the proportionality as alternative to the solution of conflicts of basic rights, of the test in criminal proceeding, it will be presented the concept of the fortuitous meeting and the possible legal consequences of its application in the efetivação of the process as allowed test. The method will be dogmatic-prospective in the perspective of analysis of the national and foreign doctrine as well as of the national jurisprudence. The monograph considers understanding of lege lata can to adjust the Brazilian legislation, adopting, however, also as referencial Draft bill of initiative of the Ministry of Justice